An evaluation of picking routing policies to improve warehouse efficiency (2017)
This paper evaluates various routing policies (s-shape, largest gap, return and composite policies) and introduces a novel heuristic called Minimum Heuristic (MinH) to solve the picker routing problem. The performance of the routing policies and the MinH heuristic is validated by an experimental design, varying the number of aisles, locations per aisle and pick list size. The experimental results show the travel distance savings of MinH heuristic over routing policies, highlighting that for all of the instances, the MinH heuristic performs 14,3% better than the existing routing policies. © 2017, University of Novi Sad.